Chromone glycosides and phenolic glycoside from Scindapsus officinalis (Roxb.) Schott. (August 2021) - Yu, Jinqian; Zhao, Lei; Wang, Yuliang; Liu, Wei; Wang, Xueyong; Wang, Xiao
Graphical abstract: Highlights: We provided more information about the chemical constituents of Scindapsus officinalis . We found one anti-inflammatory chromone glycoside reported firstly in literature. Structures were elucidated by NMR, mass spectrometry and acid hydrolysis methods. Abstract: Phytochemical and pharmacological investigations of the plants of Scindapsus officinalis (Roxb.) Schott, rendered the isolation of two new chromone glycosides and one phenolic glycoside, named officinalisides F, G (1, 2) and 4- O -[ α -l -rhamnopyranosyl-(1–3)- β -d -glucopyranosyl]-( E )-3-(4-hydroxy-3-methoxyphenyl) acrylic acid (3). Structures of the three undescribed compounds were elucidated by NMR spectroscopic and acid hydrolysis experiments. All isolates were evaluated for anti-inflammatory activity against nitric oxide (NO) production assay in vitro . As indicated in the results, compound 2 exhibited significant NO inhibitory effects with IC50 value of 8.02 μM, while the other two ones showed weak NO inhibitory activities.